PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF ESBL PRODUCING KLEBSIELLAE ISOLATED FROM CLINICAL SPECIMENS IN A NIGERIAN TERTIARY HOSPITAL - Fadeyi, A.; Zumuk, P. C.; Raheem, R. A.; Nwabuisi, C.; Desalu, O. O. (African Journal of Infectious Diseases (AJID), 2015)
Background: Infection by Extended Spectrum Beta Lactamases (ESBLs) producing bacteria is a threat to man as a consequence of treatment challenges. This study evaluated the prevalence and antimicrobial susceptibility pattern of ESBL producing Klebsiellae (EPK) in clinical specimens at the University of Ilorin Teaching hospital, Ilorin (UITH), Nigeria. Methods: ESBL production was assayed using Double Discs Synergy Test (DDST). Antimicrobial susceptibility was performed by Modified Kirby-Baeur method with the organism tested against ceftazidime (30µg), cefotaxime (30µg), amoxicillin-clavulinic acid (20/10µg), cefepime (30µg), ciprofloxacin (5µg), gentamicin (10µg), trimethoprim-sulphamethoxazole (23.75/1.25µg), imipenem (10µg) and doripenem (10µg) (Oxoid, UK).Results: Fifty (26.7%) of the 187 Klebsiellae studied were EPK comprising of 37(26.8%) Klebsiella pneumoniae and 13(26.5%) Klebsiella oxytoca. There was no significant difference (p = 0.873) in ESBL production between Klebsiella pneumoniae and Klebsiella oxytoca. EPK were mostly from wound specimens (24.0%) although Klebsiellae were mostly occurring in sputum (26.2%). The EPK were resistant to ceftazidime (100%), cefotaxime (94.0%), trimethoprim-sulphamethoxazole (92.0%), gentamicin (70.0%) and ciprofloxacin (70.0%) but 100% susceptible to both doripenem and imipenem. Conclusion: The prevalence of EPK in this study is high and they are multi-drug resistant. Carbapenems are the best antibiotic treatment option for infections arising from these organisms although a coordinated rational usage is desired along with functional antibiotic prescription policy to avoid treatment failures. Continuous surveillance for ESBL producing Klebsiellae and resistance monitoring are necessary routine to strengthen infection control policies.